CINEMATIC NARRATION OF THE REALITIES OF SELF: A FOUCAULDIAN PERSPECTIVE - A.M, Mallikarjun (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This is one of the most provocative and intriguing question ever since the inception of human sciences to which philosophers, psychologists, social psychologists, sociologists, anthropologists, political scientists etc. have been responding in various ways. The question itself posed in a manner that it reflects the inability of the man to know his own Self in an objective manner. In a way, identity constructions often starts with the very same problem “Who am I?” which means that the explorations of the foundational elements that gives knowledge about the idea of self is necessary starting point for any theory of identity. However, what is equally important is to try and unravel the processes through which idea of self gets materialized in a particular fashion in certain context which hints towards the possibilities of the subjectivities within the idea of self. Here, two important propositions of Mitchel Foucault becomes salient that explores the ‘construction of self’ and ‘invention of self in societal framework’. Foucault argues, that Self is constructed by the ‘technologies of power’ and it can be invented by the ‘technologies of self’. However, construction and invention are not two independent processes but it is an interaction between the power and the resistance. This article would try and understand the two theoretical propositions with reference to the Bollywood Cinema Dear Zindgi. The film portrays how the binary oppositions are produced, and manipulated by the technologies of power which eventually constructs the idea of self within a social/cultural context and in what ways, technologies of self is a necessary catalyst for the invention of self.